The efficiency of novel enzymes in the removal of thermophilic bacilli biofilms from a stainless steel surface : a thesis presented in partial fulfilment of the requirements for the degree of Master of Food Technology, Massey University, Palmerston North - Nam, Yurina (Massey University, 2020)
Background: Biofilms, an agglomerated microbial association produced from adherence of bacterial cells on a surface, pose substantial bacterial contaminations in the dairy industry. In particular, spore-forming thermophilic bacilli, which survive heat treatments, have been identified to be the abundant biofilm formers and contaminants in dairy products. The conventional cleaning regime, Clean-In-Place (CIP), widely adopted in the industry has been proven to lack hygienic performance on the removal of these biofilms. As a sustainable alternative, more researchers have been investigating enzymes such as proteases and amylase to use as a cleaner in the recent years. However, the majority of the studies conducted have cantered around the use of amylase and proteases at a basic pH at around 60°C on non-spore forming mesophilic or psychrophilic biofilms. Aim: To examine the efficacy of novel enzymes (protease, amylase and endoglucanase) at an acidic pH and high temperature (85°C) in the removal of thermophilic bacilli biofilms (A. flavithermus, B. licheniformis and G. stearothermophilus) from a stainless steel surface. Methods and results: A. flavithermus, B. licheniformis and G. stearothermophilus were initially screened for strong biofilm forming strains. Using Plackett-Burman experimental design, enzymes were screened on the strains on stainless steel coupons determined by plate and spore counts, and impedance microbiology. Following statistical analysis, amylase and protease for A. flavithermus, and protease and endoglucanase for G. stearothermophilus were found to be significant in reducing bacterial cells. As no statistical analysis could be performed on B. licheniformis with the data obtained, protease and amylase were selected to be tested on B. licheniformis strains for further microscopy analysis. The enzymes were further examined on biofilms developed in a biofilm reactor in a batch mode based on plate and spore counts, impedance microbiology and microscopic techniques (epifluorescence microscopy and Scanning Electron Microscopy). The results demonstrated the efficiencies of amylase, protease, and the combination of amylase and protease for A. flavithermus and B. licheniformis, and endoglucanase for G. stearothermophilus. As a conformational experiment, the enzymes were investigated on the removal of biofilms formed in the continuous flow biofilm reactors, and the results confirmed and attested to the efficiencies of the enzymes. Conclusions: The results revealed that amylase, protease (CB14057) and the combination of amylase and protease for A. flavithermus and B. licheniformis, and endoglucanase (CB13961) for G. stearothermophilus had a significant impact on reducing biofilm cells (2-3 log reduction depending on the flow system adopted) and Extracellular Polysaccharides Substances (EPS). Significance and impact of the study: The present study widens the knowledge in the role of enzymes on the removal of spore-forming thermophilic bacilli biofilms in dairy processing. The structures and biofilm matrices of the tested thermophiles are yet to be known, however, this will form the basis of the future research directions.
Keywords: 310701 Bacteriology